Port competition and welfare effect of strategic privatization - Achim Czerny; Felix Höffler; Se-il Mun (Institute of Energy Economics at the University of Cologne (EWI), 2013)
Private operation of port facilities is becoming increasingly common worldwide and many governments consider the privatization of public ports as a policy option. We investigate the effect of port privatization in a setting with two ports located in different countries, serving their home market but also competing for transshipment traffic from a third region. Each government chooses whether to privatize its port or to keep port operations public. We show that there exist equilibria in which the two governments choose privatization. In these equilibria, national welfare is higher relative to a situation where both ports are public. Since port charges are strategic complements, privatization can act as a valuable precommitment tool for the two governments and allows for a better exploitation of the third region. However, from the perspective of maximizing the joint national welfare of both port countries, there is an inefficiently low incentive to privatize. It is also shown that a country with a smaller home market has a larger incentive to choose private port operation.
Keywords: L11; L90; L98; 330; Regulation; commitment; capacity markets; transmission system investment